1999
DOI: 10.1017/s1047951100005370
|View full text |Cite
|
Sign up to set email alerts
|

Reduced frequency of occlusion of aorto-pulmonary shunts in infants receiving Aspirin

Abstract: Aspirin reduced effectively the rate of occlusion of systemic-to-pulmonary arterial shunts, and should be continued as long as the shunt is in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Centazzo et al 11 showed no difference in shunt patency index (angiographic Gore-Tex diameter/preoperative Gore-Tex diameter) between patients receiving ASA and those not receiving ASA. Motz et al 10 showed that ASA reduced the incidence of partial or complete shunt occlusion in a study of 37 infants (ASA, 13%; no ASA, 54%). This finding, however, was not confirmed in a larger study conducted by Al Jubair et al 5 of 546 shunts in 478 patients (ASA, 7%; no ASA, 11%; PϭNS).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Centazzo et al 11 showed no difference in shunt patency index (angiographic Gore-Tex diameter/preoperative Gore-Tex diameter) between patients receiving ASA and those not receiving ASA. Motz et al 10 showed that ASA reduced the incidence of partial or complete shunt occlusion in a study of 37 infants (ASA, 13%; no ASA, 54%). This finding, however, was not confirmed in a larger study conducted by Al Jubair et al 5 of 546 shunts in 478 patients (ASA, 7%; no ASA, 11%; PϭNS).…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8] In addition, despite an overall reduction in mortality for single-ventricle palliation procedures in the current era, shunt thrombosis and interstage attrition remain significant problems. 9 Although the use of aspirin (ASA) was reported to reduce the rate of occlusion of aortopulmonary shunts in a small case series of 37 infants, 10 its efficacy was not confirmed in a larger study of 478 patients. 5 The purpose of the present study was to evaluate the morbidity and mortality of infants with systemic-to-pulmonary shunts and the effect of ASA use on these outcomes.…”
Section: Editorial P 236 Clinical Perspective P 297mentioning
confidence: 99%
“…In another, much smaller case study, aspirin was reported to decrease the incidence of stent thrombosis after MBTS surgery. 295 Mullen et al 296 …”
Section: 2-23 Renal Vein Thrombosis In Neonatesmentioning
confidence: 99%
“…Although antiplatelet therapy has been studied extensively in adults, evidence for its benefit in infants and young children is limited . While the use of aspirin was associated with a reduction in ECS thrombosis in some studies, others have failed to demonstrate a beneficial effect . In theory, aspirin alone may be insufficient to prevent arterial thrombosis because it inhibits only one pathway (cyclo‐oxygenase) of platelet activation, and would have minimal effect in treating thrombi that would be expected in ECS.…”
Section: Discussionmentioning
confidence: 99%